Evaluating Large Language Model Quality in Resource-Constrained Environments: An Educational Stakeholders’ Survey on Accuracy, Completeness, and Readability in Brazil - Barros, Aristoteles Peixoto; Dermeval, Diego; Rodrigues, Luiz (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2025: Anais Estendidos do XIV Congresso Brasileiro de Informática na EducaçãoDO - 10.5753/cbie_estendido.2025.13110, 2025)
Este artigo não possui um resumo.